2007
DOI: 10.1037/h0100611
|View full text |Cite
|
Sign up to set email alerts
|

Within-session changes in the preratio pause on fixed-ratio schedules of reinforcement.

Abstract: Performances under fixed-ratio schedules of reinforcement are characterized by a "post-reinforcement" or "preratio" pause that precedes responding for the reinforcer. This paper summarizes views on the origins of pausing and presents a series of molecular analyses that shed new light on the conditions under which pausing occurs. Among the findings are that pausing is not limited to the delay before the first response of the ratio and that pause durations increase over time (in some cases more than doubling acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(41 reference statements)
0
0
1
Order By: Relevance
“…1 C , E ), which is qualitatively consistent with postreinforcement pauses (Felton and Lyon, 1966) and the frustrative effects of reward omission (Amsel, 1958) long observed in other tasks in which animals receive reward on only a fraction of responses. The temporal effects here are much shorter than past studies, and other reported pauses seem to depend on prospective motoric requirements rather than past actions (Derenne and Flannery, 2007); it is therefore difficult to compare this aspect of our data to previous studies that have largely omitted the type of barriers we have used. As we show later, the longer ITIs after rewarded trials very likely involve the time spent licking and consuming the reward.…”
Section: Resultscontrasting
confidence: 70%
“…1 C , E ), which is qualitatively consistent with postreinforcement pauses (Felton and Lyon, 1966) and the frustrative effects of reward omission (Amsel, 1958) long observed in other tasks in which animals receive reward on only a fraction of responses. The temporal effects here are much shorter than past studies, and other reported pauses seem to depend on prospective motoric requirements rather than past actions (Derenne and Flannery, 2007); it is therefore difficult to compare this aspect of our data to previous studies that have largely omitted the type of barriers we have used. As we show later, the longer ITIs after rewarded trials very likely involve the time spent licking and consuming the reward.…”
Section: Resultscontrasting
confidence: 70%